REALIZATION OF PRODUCTIVE POTENTIAL OF LUPINE (LUPINUS ANGUSTIFOLIUS) AND SORGHUM IN DIFFERENT CROP ROTATIONS USING VARIOUS CULTIVATING TECHNOLOGIES - E. I. Isaeva; A. I. Artyukhov (Зерновое хозяйство России, 2018)
The research of lupine was carried out on grey forestry soil of south-west of Non-Blacksoil of Bryansk region in 2009-2012 to study productivity and basic forage traits of lupine (Lupinus angustifolius) grain and soybean in different crop rotations using various cultivating technologies. The scheme of the experiment consisted of 6 crop rotations (spring rape-lupine (soybean); spring rape-lupine (soybean)-barley; spring rape-lupine (soybean)-barley-winter rape- lupine (soybean)-spring wheat). Each rotation of crops was studied on the background of three technological schemes (alternative, reasonable, intensive) which differ in application of chemicals. In all crop rotations lupine didn’t react on intensification of technologies, showing high productivity even under alternative cultivating technology. Lupine (Lupinus angustifolius) as a crop of northern ecotype can be cultivated in different soil-climatic conditions, in northern parts of Russia, receiving plant raw material with high content of protein with minimum energy expenditures for its production.